Proprioceptive deficits and postural instability in adolescent idiopathic scoliosis: a comparative study of balance control and key predictors - Koura, Ghada; Elshiwi, Ahmed Mohamed F.; Reddy, Ravi Shankar; Alrawaili, Saud M.; Ali, Zeinab A.; Alshahrani, Mazen Abdullah N.; Alshahri, Amer Abdullah M.; Al-Ammari, Sultan Sarhan Z. (Frontiers in Pediatrics, 2025)
BackgroundAdolescent idiopathic scoliosis (AIS) is associated with postural instability, which may be influenced by proprioceptive deficits. While previous studies have examined balance impairments in scoliosis, the extent to which proprioception errors contribute to postural instability remains unclear. Understanding this relationship is crucial for developing targeted rehabilitation strategies.ObjectivesThis study aimed to assess proprioceptive accuracy and postural stability in individuals with AIS compared to healthy controls and identify key predictors of postural instability.MethodsThis cross-sectional study included 60 participants (30 with AIS, 30 controls). Postural stability was assessed using the Biodex Balance System (BBS), measuring Overall Stability Index (OSI), Anterior-Posterior Stability Index (APSI), Medial-Lateral Stability Index (MLSI), Center of Pressure (COP) displacement, and Reaction Time. Lumbar proprioception errors in flexion and extension were evaluated using an inclinometer-based joint repositioning test.ResultsThe AIS group showed significantly greater COP displacement (p = 0.013) and lumbar proprioception errors in flexion (p = 0.021) and extension (p = 0.004) compared to controls. Regression analysis identified proprioception errors and COP displacement as significant predictors of postural instability (R² = 0.647).ConclusionIndividuals with scoliosis exhibit significant proprioceptive deficits, which strongly correlate with postural instability. These findings highlight the importance of proprioceptive training in scoliosis rehabilitation to improve balance control.